If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + 4n = 3n + 3 Reorder the terms: 8 + 4n = 3 + 3n Solving 8 + 4n = 3 + 3n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-3n' to each side of the equation. 8 + 4n + -3n = 3 + 3n + -3n Combine like terms: 4n + -3n = 1n 8 + 1n = 3 + 3n + -3n Combine like terms: 3n + -3n = 0 8 + 1n = 3 + 0 8 + 1n = 3 Add '-8' to each side of the equation. 8 + -8 + 1n = 3 + -8 Combine like terms: 8 + -8 = 0 0 + 1n = 3 + -8 1n = 3 + -8 Combine like terms: 3 + -8 = -5 1n = -5 Divide each side by '1'. n = -5 Simplifying n = -5
| C=3.14xr | | 30.24/x | | 12n-3=n+15 | | 2(3x-6)=-24 | | a-16=-15 | | 12n-3=n+13 | | 9x+5x=-84 | | (Y+10)4= | | -15k=240 | | 12x^(-2/5)-19x^(-1/5)-11=0 | | 2x^4-14x^3-36x^2=0 | | x^2+0x+5=0 | | m+2-6m=2+3m | | 8+[9t+4]= | | 5z-5(3-2z)=60 | | 5.5-4= | | -7y-5x=14 | | 6(6x+5)=35x+11 | | 9(x+2y)-(5x+4y)= | | 3+2c+2c=12 | | 0-10=7x | | 7+9x+2=2x+19+6x | | 3x^2+x+5=1 | | -9=v-19 | | -t/-9=2- | | 2x-6=-4x+12 | | -9a+4=-6a+-17 | | 7(1x+3)-5x=49 | | x-b=m(y-a) | | -28=b-19 | | x+1=1-4x-x | | 3-2(n-4)= |